The scientific method as a pedagogical resource in the final years of high school: Doing science in biology class - Diego Rasilla, Francisco Javier (Pulso. Revista de educación, 2004)
The article advocates for educational innovation in the teaching of experimental sciences in post-16 education in Spain. It details a pedagogical experience that aligns with the current mode of producing current scientific knowledge. This experience involves encouraging students to conduct directed research work that enables them to question reality by formulating hypotheses and designing experiments. By encouraging the students to engage in research work and experiment design, the pedagogical experience aims to cultivate scientific curiosity among the students. It also helps them develop several intellectual skills and attitudes inherent in scientific research that are beneficial beyond the scientific field. This approach to teaching experimental sciences not only enhances students' scientific skills but also can form part of their citizenship education.